Impact of Management Leadership on Organizational Performance of Trading Sector Public Enterprises in Nepal - Panthi, Rishikesh (Journal of Nepalese Business Studies, 2025)
Management leadership has been a central position in management to determine organizational performance nowadays. Visionary leadership is essential for establishing the vision and mission, defining and setting objectives, and formulating policies, programs, methods and strategies, directing and coordinating all activities within different departments efficiently and effectively, creating an enthusiasm in employees to meet the vision, mission, and objectives along with changes in the business's external environment, can only be achieved with effective leadership. Organizational performance refers to an organization's capacity to accomplish such goals and objectives such as high profit, quality product, financial profitability, operational efficiency, shareholder satisfaction, and survival at a pre-determined period using an appropriate strategy for action. The study aims to examine the impact of management leadership on the organizational performance of the trading sector PEs in Nepal. A descriptive and causal comparative research design is used to describe different phenomena of the dependent and independent variables in this research. Primary data were collected from structured questionnaires from 134 out of 196 respondents, including officer-level employees of 5 trading sector PEs, by a stratified random sampling method. Some key informants were interviewed. The findings of the study show that the level of performance of the trading sector public enterprises was found below the satisfactory level due to weak management leadership. The findings of the study are very helpful to the government of Nepal, concerned authorities, stakeholders, Employees and heads of PEs, policy makers, researchers, academician, and experts for their further study in this subject matter.